2005
DOI: 10.1021/la051457v
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Surface Wettability of a Tethered DNA Base

Abstract: We show that the DNA base thymine and other uracil derivatives, when alkylated with a hydrocarbon chain and assembled at a gold interface, dimerize when subjected to UV irradiation. The process is robust and reversible and is accompanied by a substantial decrease in wettability as well as a marked decrease in acidity constant when the dimer is formed. There is a concerted molecular reorientation that accompanies photodimerization, with the dimer displaying a marked affinity for the gold surface. The spatial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…Both UV-vis and FTIR spectra confirmed that the photodimerization of terminal thymine molecules under 280 nm light irradiation occurred on 7.0 nm gold particles in pH 12.5 water and 2.2 nm particles in a DMF/H 2 O mixture. During photodimerization, the orientation of thymine molecules on the gold surface is changed and as a consequence the gold surface becomes more hydrophobic when the dimer is present similar to those observed on flat gold surfaces [54]. It is proposed that the change in hydrophobicity is sufficient to trigger the aggregation of the 7.0 nm gold particles in high-pH water and ultimately lead to the coagulation of the suspension (see Fig.…”
Section: Manipulation Of Colloid Stability With External Stimulimentioning
confidence: 91%
See 2 more Smart Citations
“…Both UV-vis and FTIR spectra confirmed that the photodimerization of terminal thymine molecules under 280 nm light irradiation occurred on 7.0 nm gold particles in pH 12.5 water and 2.2 nm particles in a DMF/H 2 O mixture. During photodimerization, the orientation of thymine molecules on the gold surface is changed and as a consequence the gold surface becomes more hydrophobic when the dimer is present similar to those observed on flat gold surfaces [54]. It is proposed that the change in hydrophobicity is sufficient to trigger the aggregation of the 7.0 nm gold particles in high-pH water and ultimately lead to the coagulation of the suspension (see Fig.…”
Section: Manipulation Of Colloid Stability With External Stimulimentioning
confidence: 91%
“…Photocontrolled, reversible contact angle changes as a consequence of the photoreaction of thymine occurring on surfaces were observed [53,54]. Mixed monolayer capped gold nanoparticles containing thymine moieties were prepared recently for the assembly of gold particles into nanostructures via photoreaction of thymine or molecular recognition [55,56].…”
Section: Formation and Structure Of Self-assembled Monolayer Protectementioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is due to the mechanism that involves photogenerated electrons and holes as well as absorbed water 17. In addition, several kinds of organic compounds and their derivates, such as azobenzenes, spiropyrans (SPs), and cinhamates,18–24 have a photoinduced transformation between two chemical configurations. This may lead to the changes of molecular polar and surface‐free energy that result in a transition of surface wettability accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists have long tried to reproduce these dynamic biological events and have recently made an important step in that direction by creating artificial stimuli-responsive surfaces [3][4][5][6][7]. These smart substrates present modulatory surface properties that are able to respond to external chemical/biochemical [8][9][10][11][12], thermal [13][14][15], electrical [16][17][18][19][20], and optical stimuli [21][22][23][24][25][26][27][28][29][30][31]. Due to their dynamic nature such substrates are very appealing for applications in the biomedical field [32].…”
mentioning
confidence: 99%